2015
DOI: 10.1074/jbc.m115.658864
|View full text |Cite
|
Sign up to set email alerts
|

Systemic RNA Interference Deficiency-1 (SID-1) Extracellular Domain Selectively Binds Long Double-stranded RNA and Is Required for RNA Transport by SID-1

Abstract: Background: Systemic RNA interference deficiency-1 (SID-1) is a membrane protein required for cellular uptake of RNA in C. elegans. Results: SID-1 extracellular domain selectively binds long dsRNA. Conclusion: Binding affinity between SID-1 ECD and dsRNA is related to RNA transport efficiency by SID-1. Significance: This defines SID-1 ECD as a functional domain for dsRNA recognition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(90 citation statements)
references
References 34 publications
7
83
0
Order By: Relevance
“…To assess interaction between SIDT2 and internalised poly(I:C), we performed fluorescence resonance energy transfer (FRET) analysis by time domain fluorescence lifetime imaging microscopy (FLIM), and observed a significant reduction in fluorescence lifetime for poly(I:C)-fluorescein in the presence of SIDT2-mCherry. This indicates a likely molecular interaction between SIDT2 and poly(I:C) (Figure 1C), and is consistent with the recent demonstration that the extracellular domain of mouse SIDT2 can bind dsRNA in vitro (Li et al, 2015a). To test the specificity of this interaction, we performed the same experiment using dsDNA, which also appeared to co-localise with SIDT2-mCherry following internalisation (Figure 1B).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…To assess interaction between SIDT2 and internalised poly(I:C), we performed fluorescence resonance energy transfer (FRET) analysis by time domain fluorescence lifetime imaging microscopy (FLIM), and observed a significant reduction in fluorescence lifetime for poly(I:C)-fluorescein in the presence of SIDT2-mCherry. This indicates a likely molecular interaction between SIDT2 and poly(I:C) (Figure 1C), and is consistent with the recent demonstration that the extracellular domain of mouse SIDT2 can bind dsRNA in vitro (Li et al, 2015a). To test the specificity of this interaction, we performed the same experiment using dsDNA, which also appeared to co-localise with SIDT2-mCherry following internalisation (Figure 1B).…”
Section: Resultssupporting
confidence: 91%
“…5′ PPP) of viral RNAs facilitate the discrimination between self and non-self by host RNA sensors such as RIG-I, it will also be interesting to investigate whether any modifications facilitate SIDT2-dependent RNA transport. Similarly, dsRNA length is a key determinant of recognition by RIG-I, MDA-5 and TLR3 (Kato et al, 2008; Leonard et al, 2008), and SIDT2 was recently reported as having a higher binding affinity for longer dsRNAs (300–700 bp) (Li et al, 2015a). Functional investigations to determine whether SIDT2 can transport shorter substrates such as siRNAs may shed light on the development of more effective RNAi therapeutics, whose delivery continues to be hindered by poor endosomal escape (Dominska and Dykxhoorn, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of a mutant SID-1 to interfere with the function of a wild-type SID-1 protein suggests that SID-1 functions as a multimer (Shih et al, 2009). The extracellular domain of SID-1 and its human homologs selectively bind dsRNA (Li et al, 2015) and preliminary structural analyses of the extracellular domain of human SID-1 suggest a tetrameric structure that could enable the end-on entry of dsRNA into cells (Pratt et al, 2012). Together, these observations could explain the ability of SID-1 to discriminate between dsRNA and RNA/DNA hybrids (Shih and Hunter, 2011).…”
Section: Import Into Cellsmentioning
confidence: 99%
“…The success of this approach is in part due to the systemic nature of RNAi (sysRNAi) in the worms À that is, interfering RNA can spread throughout the organism and elicit RNA in different tissues. Uptake and export of dsRNA is via dsRNA gated channel proteins: the membrane protein SID-2, expressed in apical intestinal cells, is responsible for dsRNA uptake in the gut [15], and then further systemic spread throughout the worm is believed to be due to cellular export of dsRNA by SID-5 [16,17] and uptake by adjacent cells via the extracellular domain of SID-1 [18]. Moreover, RNAi is amplified through RNA-dependent RNA polymerase activity (RdRp) [7].…”
Section: Rnai Is Used As a Research Tool In Model Invertebratesmentioning
confidence: 99%